Farm Management and Factors Influencing Farmers' Adaptation Strategies in the Serayu Dam Area to Climate Change - Mulyani, Altri; Wijayanti, Irene Kartika Eka; Saputro, Wahyu Adhi; Sarno, Sarno; Sukmaya, Syahrul Ganda (Universitas Panji Sakti, 2024)
Unpredictable climate change impacts several sectors, one of which is the agricultural sector. Extreme climate change causes a decrease in farmer production. The Serayu movable dam area is an area that is prone to flooding, where farmers around this area own land. Farmers can make anticipatory efforts to overcome losses farmers suffer to adapt to the management system and farmer resilience. This study aims to analyze the farm management and factors influencing farmers' adaptation strategies to climate change in the Serayu Dam area. The research was conducted using a descriptive quantitative analytical method. This study used 30 rice farmers as respondents in the Serayu movable dam area. The data analysis method used farm business analysis and logistic regression. The results of the study also stated that the rice farming carried out by farmers earned a profit of IDR 7,639,324 with a total income received by farmers of IDR 10,726,000 and a total farmer expenditure of IDR 3,086,676. Farmers in the Serayu movable dam area have also experienced a decrease in crop production due to climate change. The adaptation strategy carried out by farmers is to postpone or advance planting based on the pranoto mongso used. The results of the study also stated that factors influence farmers' adaptation strategies, namely farmer education, farmer experience, farmer profession as the main job and farmer activity in farmer groups.